The Influence of Islamic Education on Halal Lifestyle Awareness in Muhammadiyah Junior High School - Handayani, Puspita; Mudlofir, Ali; Bakar, M. Yunus Abu (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2024)
The purpose of this study was to determine the correlation between halal knowledge and the halal lifestyle of Muhammadiyah junior high school students in East Java. This study used quantitative methods with a correlation data analysis model using SPSS statistical 19 software to analyze questionnaires that have been distributed to 261 students from two schools, those SMP Muhammadiyah 1 Sidoarjo and SMP Muhammadiyah 12 Gresik Kota Baru. From the results of the analysis, it was found that a significant correlation of 0.01 means that the correlation is very strong between students' halal knowledge and their halal lifestyle. Conditions in the field of material about halal in Islamic Religious Education subjects are very minimal, from curriculum analysis found halal material in the eighth grade of even semesters on the theme of the Qur'an recognizes verses and hadiths about halal food. From this study, it was found that students' halal lifestyle was determined by how they acquired knowledge, of which 88.9% of students' halal knowledge was obtained from PAI lessons at school. So that a learning model is needed that leads to a 21st century learning model, one of which is with the Project Based Learning (PjBL) model, real project-based learning in life.